(untitled) (Revista do Centro de Estudos Portugueses, 2005)
O presente trabalho estuda a construção do movimento da Poesia Experimental Portuguesa, que teve um papel importante na renovação estética na literatura dos anos 60, contribuindo para um debate internacional em torno dos movimentos de poesia experimental e, a partir deste mesmo debate, propondo um caminho de liberdade criativa, frente ao quadro político reinante em Portugal. Destacamos, neste contexto, a importante participação da Poesia Concreta brasileira como estímulo a esta abertura estética. This work studies the construction of the Portuguese Experimental Poetry that had a great part in the aesthetic renewal in the literature of the sixties, contributing to an international debate around the movements of experimental poetry and, because of this, proposing an opening for the creative freedom, in the presence of the political and cultural situation in Portugal in these years. We highlighted, in this context, the important participation of the Brazilian Concrete Poetry as incentive for this aesthetic opening.